Implementation of Health Education with Demonstration Methods through Short Education Movie (SEM) Media to Increase the Knowledge and Attitudes in Overcoming the Impact of Online Game Addiction - Liklikwatil, Nelma; Imlabla, Floria Veramaya; Wiguna, Paramita Kurnia; Hairat, Ummul; Latuconsina, Nur Aisah (Indonesian Journal of Global Health Research, 2024)
Online game addiction has become a significant health problem. The use of short film media as a health education tool to overcome game addiction with interesting and relevant content can attract the attention of young audiences who are more interested in visual and interactive media. Seeing the existing problems, this research is aimed at analyzing the influence of Health Education using demonstration methods through short educational films in overcoming the impact of online game addiction. This research is a quantitative research with a quasi-experimental pretest-protest design. This research will be carried out at Ambon vocational high schools. The selection of this research location was based on the consideration of having a basic understanding of health topics so that it could provide more valid and useful data. The population in this study was students. Sampling using random sampling technique obtained 40 students. Data was collected using knowledge questionnaires and attitude questionnaires to measure before and after the intervention. The statistical test used is the Wilcoxon signed Rank test. Results: The research results showed that there was a significant influence of knowledge and attitudes through short film media in overcoming online game addiction. The results of the Wilcoxon signed Rank test analysis show the same value for both variables, namely a p-Value of 0.000. There is a significant influence in applying the short film method in increasing knowledge and attitudes in overcoming online game addiction.